2022
DOI: 10.3389/fnagi.2022.830729
|View full text |Cite
|
Sign up to set email alerts
|

Higher Dementia Risk in People With Gastroesophageal Reflux Disease: A Real-World Evidence

Abstract: BackgroundWhether or not patients with gastroesophageal reflux disease (GERD) have a higher risk of developing subsequent dementia remains unknown, and no observational evidence from population-based data is available. This study was to determine whether patients with GERD have a higher future risk of developing dementia.MethodsFor the period 2000–2012, datasets from the Longitudinal Health Insurance Database (LHID, subset of National Health Insurance Research Database in Taiwan) were analyzed. Definition of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…In a reverse MR analysis, GERD demonstrated a signi cant causal association with decreased cognitive function. This nding suggests that genetic predisposition to GERD contributes to an increased risk of cognitive dysfunction which may partly explain the previous ndings of a positive association and genetic correlation between GERD and AD or dementia [7,11]. Although, in more conservative sensitivity testing, the signi cance of this nding waned and was no longer evident, together, the results of our follow-up analysis are more supportive of a putative causal effect of GERD on cognitive traits than otherwise.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In a reverse MR analysis, GERD demonstrated a signi cant causal association with decreased cognitive function. This nding suggests that genetic predisposition to GERD contributes to an increased risk of cognitive dysfunction which may partly explain the previous ndings of a positive association and genetic correlation between GERD and AD or dementia [7,11]. Although, in more conservative sensitivity testing, the signi cance of this nding waned and was no longer evident, together, the results of our follow-up analysis are more supportive of a putative causal effect of GERD on cognitive traits than otherwise.…”
Section: Discussionsupporting
confidence: 63%
“…Similar to the growing evidence linking AD with GIT traits [7][8][9][10][11][12][13][14], emerging ndings from conventional observational studies suggest a range of GIT disorders are associated with cognitive dysfunction [20][21][22][23]. For instance, a recent systematic review and meta-analysis, of cross-sectional studies, reported a signi cant risk of cognitive impairment (including de cits in attention, executive function, and working memory), in individuals with in ammatory bowel disease (IBD), compared to controls [20].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…To address the issue, we only included those patients with more than two out-patient visits or one inpatient visit for hypothyroidism as our outcome event to validate the definition. The applied codes for diseases of interest and related comorbidities have also been utilized in previous real-world studies [ 15 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Longitudinal Health Insurance Database (LHID), a sub-dataset from the Taiwanese National Health Insurance Research Database (NHIRD), has been utilized in the current study. The NHIRD is a database based on a compulsory National Health Insurance program in Taiwan, which has a greater than 90% coverage and has been widely utilized in previous studies [ 14 , 15 , 16 ]. Information regarding patients’ hospitalization, diagnostic records, urbanization and income data were available in the LHID.…”
Section: Methodsmentioning
confidence: 99%